ON THE ICE-STORAGE CHARACTERISTICS OF CATLA CATLA AND LABEO FIMBRIATUS - BANDYOPADHYAY, J k; CHATTOPADHYAY, A K; BHATTACHARYYA, S K (Fishery Technology, 2017)
The ice-storage characteristics of Catla catla and Labeo fimbriatus are reported. Muscle pH, moisture, total volatile nitrogen, alpha amino nitrogen and peroxide value and also the changes in total bacterial count are srndied. C. catla and L.fimbriatus both could be stored in ice for 18 days.